NGO Membangun Ketangguhan Petani Menghadapi Perubahan Iklim: Studi Desa Model Cerdas Iklim Dampingan BITRA Indonesia - Zega, Dicky Risman; Manalu, Dimpos; Tobing, Artha Lumban (Research and Community Service UNIVERSITAS KALBIS, 2025)
This study analyzes the role of BITRA Indonesia's Non-Governmental Organization (NGO) in building farmers' resilience to climate change through the Climate Smart Model Village program. Using a qualitative method with a case study approach, this study explores mentoring strategies and obstacles in increasing farmers' capacity, with data collected through in-depth interviews, documentation, and focus group discussions. The results of the study show that BITRA Indonesia plays a role in building farmer resilience through training, agricultural diversification, and policy advocacy, which is reflected in the increasing application of sustainable agricultural techniques by assisted farmers. However, limited government support and low interest from farmers outside the assisted groups and the younger generation are still the main challenges. Therefore, stronger collaboration between NGOs, governments, and communities is needed so that this program continues and has a wider impact in increasing farmers' resilience to climate change. . Bitra indonesia, climate change, climate smart model village, farmer resilience, non-govermental organization.